Temporal trend in the compensation claim applications for work-related COVID-19 in Italy: Compensation claims for COVID-19 in Italy - Marinaccio, Alessandro; Brusco, Adelina; Bucciarelli, Andrea; D'Amario, Silvia; Iavicoli, Sergio (La Medicina del Lavoro, 2021)
Introduction: The SARS-CoV-2 pandemic is an impacting challenge for the occupational medicine and epidemiology. The identification of occupational groups most at risk of exposure is critical in contrasting and preventing the epidemic diffusion. Objective: To analyse the compensation claim applications collected by the Italian Workers’ Compensation Authority (INAIL) for identifying the occupational patterns and the temporal trend, in comparison with general population data. Methods: Daily time series of compensation claim applications for COVID-19 injuries in the period March-October 2020, has been analysed, estimating the epidemiological parameters of interest and comparing findings with general population data.Results: In the period March-October 2020, 65,804 compensation claim applications for COVID-19 have been collected by INAIL. The ratio between compensation claims applications and COVID-19 cases in the general population appears decreasing in the period, passing from 20% in the first pandemic period (March-April) to 3-4% in the September-October period. During the summer period, an increase in male and not Italian component and a decrease in mean age, Northern regions, and health care workers contributions to the occupational claims applications have been observed. Discussion: The comparative analyses between occupational and general population data allowed to describe how the so called “second wave” of COVID-19 epidemic in Italy involved the occupational settings less than the other risk factors. There is a need to go towards an occupational surveillance system for COVID-19 infection, with the aim of monitoring and preventing the occupational risk of infection, supporting insurance system effectiveness and managing vaccination policies.